The presence of qacA/B gene in Brazilian methicillin-resistant Staphylococcus aureus - Neide H Tokumaru Miyazaki; Alessandra O Abreu; Victor A Marin; Cleide AF Rezende; Márcia TB Moraes; Maria Helena S Villas Bôas (Memorias do Instituto Oswaldo Cruz, 2007)
A total of 74 methicillin-resistant Staphylococcus aureus (MRSA) strains isolated from three government hospitals in 2002 and 2003 were examined concerning the distribution of qacA/B gene, which is the determinant of resistance to quaternary ammonium compounds largely employed in hospital disinfection. By polymerase chain reaction the qacA/B gene was found in 80% of the isolates, which is a significant result considering it is the first time that qacA/B gene is being reported for Brazilian MRSA strains and it is presented at a high rate.